South Coastal Community Development: Issues and Challenges - Yuliadi, Imamudin (Universitas Muhammdaiyah Surakarta, 2013)
Reality show that Indonesia is one country that have longest beach in the world. This fact give implication that economic potential of people life at the beach is important factor to indoors economic growth for improving walfare and equity economic development both national and regional scope. Research method that applied is desriptive investigative for obtain the fact about the economic problem of people at the beach especially beach potential economy for improving people economic welfare. Analitical methode at this research is location quotion (LQ), shift-share, and typology klassen. The output of this research is making the planning model of promotion system and integrated investment to realize the equality of development economic at beach are in Yogyakarta.